2017
DOI: 10.1016/j.vaccine.2016.11.033
|View full text |Cite
|
Sign up to set email alerts
|

A systems approach to vaccine decision making

Abstract: Vaccines reside in a complex multiscale system that includes biological, clinical, behavioral, social, operational, environmental, and economical relationships. Not accounting for these systems when making decisions about vaccines can result in changes that have little effect rather than solutions, lead to unsustainable solutions, miss indirect (e.g., secondary, tertiary, and beyond) effects, cause unintended consequences, and lead to wasted time, effort, and resources. Mathematical and computational modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…As a result, they are more inclined to make a decision according to the "forgotten benefits and overstated risk" principle, which may increase their doubts about performing immunisation [6] -especially if they derive such information from unreliable non-medical sources. The conducted research confirmed that a doctor and health service have ceased to be the only source of information about vaccinations, which is confirmed in the literature [7]. Talks with one's family or friends, as well as the Internet and visited Internet forums have also gained importance.…”
Section: Discussionsupporting
confidence: 70%
“…As a result, they are more inclined to make a decision according to the "forgotten benefits and overstated risk" principle, which may increase their doubts about performing immunisation [6] -especially if they derive such information from unreliable non-medical sources. The conducted research confirmed that a doctor and health service have ceased to be the only source of information about vaccinations, which is confirmed in the literature [7]. Talks with one's family or friends, as well as the Internet and visited Internet forums have also gained importance.…”
Section: Discussionsupporting
confidence: 70%
“…However, as these vaccine development efforts progress, it is not yet clear what vaccine efficacies are necessary to achieve this goal with a vaccine alone, thereby eliminating the need for measures such as social distancing. As described previously, 1,2 it is important to determine the efficacy thresholds to aim for early on and during a vaccine's development. This can help identify the best candidates for various roles (e.g., vaccines that can prevent or extinguish an epidemic versus reduce the impact of an epidemic) to help guide resource allocation and also properly manage expectations once each vaccine reaches the market.…”
mentioning
confidence: 99%
“…A fourth prong is to use systems methods to better diagnose coping situations and determine their impact. As we have previously indicated,8 11 12 39 without assistance, humans can struggle to understand the reverberating effects of a change throughout a complex system. Systems mapping and modelling can help elucidate and quantify such effects and identify ways to address resulting problems.…”
Section: Discussionmentioning
confidence: 99%
“…Since immunisation is crucial to protecting populations against potential life-threatening or life-altering diseases, the consequences of coping masking inadequate immunisation systems can be substantial. They can also be complex and difficult to follow unaided as immunisation supply chains are complex 11 12. Therefore, to assess the broader impact of varying degrees of coping behaviours, we developed a computational simulation model of the routine immunisation supply chain of Bihar (a state in India), where coping (in this case, making additional shipments of vaccines above stated policy) is known to occur.…”
Section: Introductionmentioning
confidence: 99%